Impact of Hearing Loss on Patient–Provider Communication Among Hospitalized Patients: A Systematic Review. (May 2019) - Shukla, Aishwarya; Nieman, Carrie L.; Price, Carrie; Harper, Michael; Lin, Frank R.; Reed, Nicholas S.
Age-related hearing loss is a highly prevalent chronic condition in older adults, but hearing loss is rarely accounted for in patient–provider communication studies. This systematic review synthesizes current evidence on the impact of age-related hearing loss on patient–provider communication in hospitalized older adults. Five databases were queried to identify original research that examined patient–provider communication in older adults with hearing loss in an inpatient setting. Of 1053 studies, 13 were included in the final review. All studies reported an adverse effect of hearing loss on patient–provider communication. Among studies that evaluated an intervention to improve communication in older adults with hearing loss, simple interventions such as low-cost voice amplifiers were found to improve communication. An understanding of the effect of hearing loss on patient–provider communication and strategies to mitigate the impact are needed in order to provide safe, quality, patient-centered care to older adults with hearing loss.